LITERATURE REVIEW: PENGARUH PRAKTIK PENGHINDARAN PAJAK TERHADAP NILAI PERUSAHAAN DENGAN TRANSPARANSI PERUSAHAAN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN SEKTOR MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - widiyati, dian; Prasanto , Shania Rizky (JURNAL AKUNTANSI DAN MANAJEMEN MADANI, 2025)
This research aims to test and analyze the effect of tax avoidance practices on company value by considering company transparency as a moderating variable. The object of this research is manufacturing sector companies listed on the Indonesia Stock Exchange (BEI). This research uses the Systematic Literature Review (SLR) method on seven published journals, taken from the Google Scholar database, from 2016 to 2022. From the research results it can be concluded that tax avoidance practices have no effect on company value. Company transparency is able to moderate the relationship between tax avoidance practices and company value. The limitation of this research lies in the use of a sample which is only limited to manufacturing sector companies listed on the Indonesia Stock Exchange (BEI) in a certain time period. Therefore, in future research it is hoped that we can develop samples from other sectors and different years to gain a more comprehensive understanding of the influence of tax avoidance practices on company value with company transparency as a moderating variable.